Physico-mechanical properties of cattle hide leather for working gloves with flame retardant addition - Iwan Fajar Pahlawan; Gresy Griyanitasari (Universitas Sebelas Maret, 2020)
Objective: Indonesian metal casting industry is a labor-oriented industry which involves thermal application in the workplace. Thus, it is essential to protect the workers for any risks during their activity. Leather gloves, as personal protective equipment, need to be manufactured that can prevent the workers from burn injured. The study aimed to analyze the effect of flame retardant addition on finished leather’s physical and mechanical properties for a specific article, i.e. working gloves.Methods: The research used pickled cattle hides and commercial flame retardant as main materials. The leather chemicals used in the process are those which is commonly used to manufacture working gloves leather article. The treatments involved the addition of commercial flame retardant in fatliquoring (2%, 4%, 6% w/w) and finishing process (100 parts, 200 parts, 300 parts). The effect of flame retardant addition on shrinkage percentage, thickness, rub fastness, tensile strength, and elongation at break, were evaluated. Descriptive analysis is applied to describe the properties of the resulted finished leather.Results: The result shows that the addition of flame retardant in fatliquoring and finishing process indicates a variation in the leather’s physical-mechanical properties. The leather, manufactured with the addition of 4% (w/w) in fatliquoring, shrunk 7.65±1.42%, had tensile strength value at 520.48±13.79 kg/cm2, good rub fastness at dry and wet basis (5 and 4/5), elongation value at 52.9±4.09%, and thickness 0.87±0.02 mm.Conclusions: it can be concluded that the use of 4% (w/w) flame retardant in fatliquoring is suggested to be the best formulation to produce working gloves leather.